2018
DOI: 10.4172/2329-6682.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of SNPs in GH, GHR, IGF-I and IGFBPII Genes and their Association with Some Productive and Reproductive Traits in Native Breeder Hens

Abstract: The aim was to study the polymorphisms in GH, GHR, IGF-I and IGFBPII genes and their association with productive and reproductive traits. DNA was extracted from blood samples of 380 breeder hens of Mazandaran native fowls breeding station by modified salting out method. For genotyping, PCR products of GH, GHR, IGF-I and IGFBPII loci were digested with specific restriction enzymes. We found six genotypes of AA, BB, CC, AB, AC and BC with the frequency of 0.10, 0.01, 0.36, 0.07, 0.34 and 0.12 in GH, two haploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A high circulating IGF-1 concentration in laying hens is related to a high egg weight [16], egg production rate [17], and feed efficiency [18]. Liu et al [19] reported that the increase of serum IGF-1 concentration in geese corresponded to the improvement of egg weight and egg production rate and the reduction of feed conversion ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high circulating IGF-1 concentration in laying hens is related to a high egg weight [16], egg production rate [17], and feed efficiency [18]. Liu et al [19] reported that the increase of serum IGF-1 concentration in geese corresponded to the improvement of egg weight and egg production rate and the reduction of feed conversion ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [ 15 ] noted that the production performance improved in laying hens fed the diet supplemented with herbal active ingredients was due to the enhancement of serum IGF-1 concentration. A high circulating IGF-1 concentration in laying hens is related to a high egg weight [ 16 ], egg production rate [ 17 ], and feed efficiency [ 18 ]. Liu et al [ 19 ] reported that the increase of serum IGF-1 concentration in geese corresponded to the improvement of egg weight and egg production rate and the reduction of FCR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this gene consequently result in three genotypes, AA (620 and 280 bp), BB (450, 280 and 170 bp) and AB (620, 450, 280 and 170 bp). The results show that the DNA banding patterns of GH was not respectively consistent with what was previously reported byTanaka et al (1992);Stephen et al (2001); orKazemi et al (2018). When studying native chicken of Iran,Kazemi et al (2018) show a PCR fragments of 776 bp; and using restriction reaction, with MspI restriction enzyme, detected polymorphism in intron 1 of GH gene.…”
mentioning
confidence: 41%
“…The results show that the DNA banding patterns of GH was not respectively consistent with what was previously reported byTanaka et al (1992);Stephen et al (2001); orKazemi et al (2018). When studying native chicken of Iran,Kazemi et al (2018) show a PCR fragments of 776 bp; and using restriction reaction, with MspI restriction enzyme, detected polymorphism in intron 1 of GH gene. The result obtained three kind of alleles of A, B and C and 6 different haplotype profiles (AA, BB, CC, AB, AC and BC).…”
mentioning
confidence: 41%
“…A similar situation was found for insulin-like growth factor I gene. In general, its functioning is directly associated with GH and GHR, so they may be viewed as a unifi ed functional system, which is more than justifi ed from a physiological standpoint (Attarchi et al, 2017;Kazemi et al, 2018). However, regardless of perspectives, the phenomenon of potential breed specifi city imposes limitations -it is not always possible to determine the association between different alleles of IGF-I and productive traits.…”
Section: Discussionmentioning
confidence: 99%